A geostatistical model for estimating edge effects and cumulative human disturbance in wetlands and coastal waters. Issue 8 (2nd August 2020) - Humphreys, John M.; Mahjoor, Amirsassan; Reiss, Kelly Chinners; Arias Uribe, Andres; Brown, Mark T.
ABSTRACT: The modification of landscapes for agriculture, residential housing, and other human uses has the potential to alter ecosystem function, reduce native biodiversity, and to diminish the capacity of natural systems to provide essential goods and services. Resultantly, methods aimed at quantifying disturbance intensity at the intersection of anthropogenic and natural lands are important to applied aspects of landscape planning and natural resource management, as well as theoretical facets of spatial ecology. Tools to appraise human disturbance in wetlands and coastal waters are especially needed because the topographic settings of surface waters make them particularly susceptible to pollutant accumulation, hydrologic alteration, and other influences from the surrounding landscape. Assuming a water resources focus, we developed a novel geostatistical method to quantify and visualize edge effects and cumulative human disturbance for all wetlands and coastal waters in the State of Florida (USA). Model validation revealed that estimated disturbance intensity was strongly correlated to species richness, levels of heavy metal contamination, and persistent organic pollutant concentration. The presented modeling framework offers a flexible means to assess human disturbance across spatial scales and could be readily applied to prioritize conservation land acquisition and to anticipate future impacts from the proposed development.